Being Byzantine Greek identity before the Ottomans - Page, Gill (Cambridge University Press, 2013)
In , the imperial city of Constantinople was captured by the troops of the Fourth Crusade, a collection of forces gathered from the states of western Europe with the ostensible aim of the liberation of Jerusalem. It was a momentous event for the citizens and subjects of the ‘Byzantine’ empire ruled from Constantinople, as their city had never before fallen to any enemy in its nine centuries of history.Having taken the capital city, the crusaders from the west went on to conquer most of the empire, although Constantinople was eventually won back fifty-seven years later, and what we now generally call the ‘Byzantine’ empire did manage to survive into the fifteenth century before its final irrevocable conquest by the Ottoman Turks.